Attitude of Jordanians towards a new enactment for an opt-out organ donation system: a cross-sectional study - Ensaf Y Almomani; Refat Aboghazleh; Silvia D Boyajian; Laila Al-Omari; Hala Awamleh; Abeer Ismail; Wejdan Abadi; Fatima Hiary; Leen Hyari; Tamara Al-Saba’a; Zaid Nsour; Mouiad Nsour; et al. (BMJ Open)
Background Organ donation entails saving or transforming lives through the provision of organs, either from living donors or deceased individuals. In Jordan, low donation rates are attributed to religious misconceptions, limited education and insufficient awareness of the burden on patients with organ failure.Objectives To investigate the attitudes of the Jordanian population towards the practicality and effectiveness of introducing an opt-out organ donation system through legislative measures, with the aim of increasing donation rates.Design This cross-sectional study used a designed self-administered questionnaire. Data were subsequently analysed using IBM SPSS software.Setting The study encompassed all 12 cities located in Jordan.Participants Data were collected from 1146 Jordanian participants, excluding individuals under the age of 18.Results Approximately 36.6% reported organ or blood donation while 18.9% participated in awareness campaigns. Many (75.7%) perceived insufficient awareness about the importance of organ donation, and 67.1% noted a scarcity of online donor registration platforms. Only 12.0% of participants discussed organ donation with healthcare providers. As anticipated, only 9.0% were registered donors while 67.7% expressed acceptance of organ donation, with 55.3% willing to enrol in donor programmes. Religion influenced 54.2% of organ donation decisions. There are associations between agreement for a new enactment and prior organ or blood donation or discussions with healthcare providers. However, religion affected willingness to donate organs. Most importantly, refusal to be a donor after death was associated with religion, occupation and awareness levels.Conclusion Despite the population’s understanding and support for the concept of organ donation, the willingness towards donating their own organs is limited. To boost organ donation rates and acceptance of the new enactment, we recommend conducting educational campaigns, improving online registration platforms, enhancing healthcare provider engagement, collaborating with religious communities and advocating for supportive policies.